Die vraag na "verstaan" in die Christologie van D Bonhoeffer - Koekemoer, J. H. (Hervormde teologiese studies, 1988)
'Understanding' in the Christology of D Bonhoeffer There has been a change in the approach to hermeneutics, with the result that it is no longer considered merely auxihary to exegesis, but is seen as a basic science, the central problem of the so-called new understanding of Scriptures. In the study of Dogmatics this opens new visions. In this regard Bonhoeffer asked certain questions, of which some are still important today. Characteristic of Bonhoeffer is that man, who has 'come of age' and is 'a-religious', is of decisive importance in the construction of a Christology. To 'save' the 'Gospel' in a world that has 'come of age', a new understanding of Scriptures is necessary, and this must be done in an a-religious way. The only question is whether he did not lose both the uniqueness of the Christian revelation and faith and the reality that is central to Christianity.